Living mulch for weed management in organic vegetable cropping systems under Mediterranean and North European conditions. Issue 3 (15th February 2016) - Ciaccia, Corrado; Kristensen, Hanne Lakkenborg; Campanelli, Gabriele; Xie, Yue; Testani, Elena; Leteo, Fabrizio; Canali, Stefano
Abstract: The aim of this study was to investigate the effect of growing in-season agro-ecological service crops as living mulch (LM) with vegetable crops, exploiting their potential to suppress weeds by filling the ecological niches otherwise occupied by weeds. Two field experiments were carried out in Denmark and Italy to compare different LM introduction strategies in organic vegetable cropping systems. In Denmark, leek ( Allium porrum L.) was grown with dyers woad ( Isatis tinctoria L.) LM strips, while cauliflower ( Brassica oleracea L. var. botrytis ) was intercropped with a broad sowed burr medic ( Medicago polimorpha L., var. a nglona ) in Italy. Two LM times of sowing relative to cash crop transplanting––an early sowing (es LM) and a late sowing (ls LM)––were compared with a control with no LM (no LM). The effects of LM treatment on crop competitiveness, LM smother effect and weed populations were evaluated by direct measurement, visual estimation and competitive index methods. Comparison among hybrid and open pollinated cultivar responses to LM introduction was also performed. Results showed a significant higher cash crop biomass in ls LM than in es LM, with comparable yield to the weeded controls, except for es LM in Italy. Moreover, in the Danish experiment, the LM and weed biomasses were up to 5 times lower in the es LM and ls LM treatments than the weed biomass alone in no LM treatment. Reduction in weed biomass and abundance was observed also in ls LM in the Italian trial. Similarly, the competitive balance (Cb ), which quantifies the ability of the cash crop to compete with neighbours, was higher in the es LM (+0.29) and ls LM (+0.72) compared with unweeded no LM control (−0.86) in Denmark. In the Italian experiment, the cauliflower showed more competitive ability against neighbours in ls LM (+0.53) and was a weak competitor in es LM (−1.51). The cash crop had higher competitive ability against LM (Cb c-lm) when sowing was more delayed in both experiments, while, in the Italian trial, the LM was more competitive against weeds (Cb lm-w) in ls LM (+1.54) than in es LM (−0.41). The slight differences observed for biomass and competitive ability between the tested cultivars, highlighted similar suitability of both hybrid and open-pollinated cultivars to grow with LM. Our findings suggest the viability of the introduced LM in managing weeds and avoiding a smother effect on the crop, with particular effectiveness with delayed LM sowing.